MODEL SPASIAL TINGKAT KERAWANAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN ROKAN HILIR - Nidya Andini; Anita Zaitunah; Samsuri Samsuri (Peronema Forestry Science Journal, 2016)
Land and forest fires in Indonesia have become the public headline which give an impact to environmental, social and economical losses. Riau is one of the region contribute to the largest smoke annually. Based on hotspot data in 2011 until 2014 from NOAA 18 and TERRA AQUA, Rokan Hilir District in Riau is one of the district with the most hotspot.  This research is aimed to find correlation between hotspot density with fire triggers factor and to find spatial model distribution of land and forest fire index in Rokan Hilir District. This research located in four sub-district, they are Bangko, Pasir Limau Kapas, Kubu and Tanah Putih sub-district. This research used GPS, ArcGIS, ArcView and  SPSS. The research method used was primary and secondary data collecting. Spatial data analysis was performed to obtain mathematical models and visualized to have a land and forest fire risk index in Rokan Hilir District.  This research show that the farm, the closest distance to road, farthest distance to city center district and the closest distance to river is the triggers factor that has the highest of hotspot density. Spatial model of land and forest fire risk is y= 0,031+0,005X1+0,006X2+0,013X3+0,004X4 with determination coeficient value is 80,4%. The highest forest fire risk is in the farm in Pasir Limau Kapas and Kubu sub-districts and the lowest is in the forest .Keywords: spatial model, land and forest fire risk index, Rokan Hilir district.